Differentiated Module to Improve Students Geometric Skill on Quadrilateral - Safrida, Lela Nur; Agustin, Nurul Wahyu; Susanto, Susanto; Setiawani, Susi; Ambarwati, Reza (Edumatica : Jurnal Pendidikan Matematika, 2026)
Geometric skills was one of the essential competencies in mathematics learning. However, instruction that did not consider differences in students’ abilities could hinder the achievement of this competency. This study aimed to produce a differentiated learning module on quadrilateral material that was valid, practical, and effective in improving students’ geometric skills. The study used the 4-D model, which included the stages of define, design, develop, and disseminate. The research subjects were 24 eighth-grade students at SMP Negeri 1 Rambipuji. Data collection techniques were questionnaire techniques and test techniques, with the included instruments being on validation sheets, teacher and student response questionnaires, pre-test, and post-test. The research results showed that the developed learning module had a validity score average of 3,84, practicality ratings of 97,50% from teachers and 83,02% from students, and an effectiveness score with an average N-Gain of 0,76 (high category). The module included learning objectives, diagnostic assessments, differentiated activities, summative assessments, and reflection. Each student group received scaffolding tailored to their ability level. This learning module could be used to support differentiated instruction aligned with the Merdeka Curriculum.